2019
DOI: 10.3847/1538-4357/ab1416
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Chemistry in Protoplanetary Disks: CS and H2CS

Abstract: The nature and abundance of sulfur chemistry in protoplanetary disks (PPDs) may impact the sulfur inventory on young planets and therefore their habitability. PPDs also present an interesting test bed for sulfur chemistry models, since each disk present a diverse set of environments. In this context, we present new sulfur molecule observations in PPDs, and new S-disk chemistry models. With ALMA we observed the CS 5 − 4 rotational transition toward five PPDs (DM Tau, DO Tau, CI Tau, LkCa 15, MWC 480), and the C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 130 publications
1
14
0
Order By: Relevance
“…A ring morphology is in agreement with observations and modelling of CS in other discs (e.g., Le Gal et al 2019), indicating that the ring is likely produced by chemical effects rather than a variation of the gas surface density or gas temperature. Our analysis shows that the ring is slightly offset from the central star, consistent with the CS emission originating from a relative height of / ∼ 0.1 in the disc.…”
Section: The Ring Of Cs Emissionsupporting
confidence: 86%
See 2 more Smart Citations
“…A ring morphology is in agreement with observations and modelling of CS in other discs (e.g., Le Gal et al 2019), indicating that the ring is likely produced by chemical effects rather than a variation of the gas surface density or gas temperature. Our analysis shows that the ring is slightly offset from the central star, consistent with the CS emission originating from a relative height of / ∼ 0.1 in the disc.…”
Section: The Ring Of Cs Emissionsupporting
confidence: 86%
“…They find the emission originates from / ∼ 0.15-0.2 (above one scale height), broadly in agreement with their model predictions of a CS reservoir between / ∼ 0.2-0.4. More recently, Le Gal et al (2019) analysed CS emission from a broader sample of discs (including DM Tau). While relative heights were not directly measured, their models show agreement with the above, placing CS reservoirs at / > 0.1.…”
Section: The Ring Of Cs Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…On Europa, the formation of H 2 SO 4 has been supposed via radiolysis from energetic charged particle bombardment and is supported both by experiments (Strazzulla et al 2007) and observations (Dalton et al 2013). Next to the presented numerous observations of sulfur molecules in space, their chemistry, especially those of organosulfur, is not well understood yet (e.g., problem of sulfur depletion in dense clouds and star-forming regions but no sulfur depletion in diffuse clouds in t h eI S M ;C a l m o n t ee ta l .2016; Le Gal et al 2019).…”
Section: Introductionmentioning
confidence: 78%
“…A hypothesis suggested that the sulfur is locked in the form of OCS in icy grain mantles (Palumbo et al 1997). A recent study has modeled that the "missing" sulfur is indeed trapped in the form of organosulfur molecules on grains (Laas & Caselli 2019).I n protoplanetary disks, the planets' places of birth around young stars, CS or H 2 CS chemistry has been discussed (Semenov et al 2018;Le Gal et al 2019). Nevertheless, the number of sulfur molecules detected in disks is significantly lower than in the diffuse ISM, indicating a high reactivity of sulfur in the gas phase (Semenov et al 2018).…”
Section: Introductionmentioning
confidence: 99%